1 Answer | Add Yours
The sum of the three roots of the given polynomial could be found using Viete's relation:
x1 + x2 + x3 = -b/a, where x1,x2,x3 are the roots of the polynomial and a,b are the coefficients of the polynomial ax^3 + bx^2 + cx + d.
We'll identify the value of the leading coefficient as a = 1 and the value of b = -3.
The sum of the roots will yields:
x1 + x2 + x3 = -(-3)/1
x1 + x2 + x3 = 3
We could solve this problem, finding the roots of the polynomial first, then calculating their sum.
x^3 - 3x^2 + 2x = 0
We'll factorize by x:
x(x^2 - 3x + 2) = 0
We'll cancel each factor:
x1 = 0
Since the sum of the roots of quadratic within brackets is 3 and the product is 2, the roots will be x2 = 1 and x3 = 2.
The usm will be x1 + x2 + x3 = 0 + 1 + 2 = 3.
Therefore, the sum of the roots of the given polynomial is x1 + x2 + x3 = 3.
We’ve answered 317,393 questions. We can answer yours, too.Ask a question